Climate Change Adaptation: Does Islamic Banking Play a Role? - Nazrul Hazizi Noordin; Faaza Fakhrunnas (Bank Indonesia, 2026)
This study examines the role of Islamic banking in advancing climate change adaptation. Applying fixed effects and System Generalized Method of Moments estimators to panel data from 29 dual banking countries from 1995 to 2021, we find that a one-standard-deviation increase in the share of Islamic banking assets is associated with a 1.773-point improvement in the climate adaptability index. When climate adaptation is decomposed into its two constituent dimensions, climate vulnerability and climate readiness, we find that Islamic banks contribute significantly to enhancing climate readiness, while their impact on reducing vulnerability is less pronounced. The contribution is particularly salient in countries where Islamic banking is systemically important, underscoring the significance of market penetration and institutional embeddedness. Additionally, Islamic banks are shown to have maintained a consistent, positive contribution to climate adaptation both before and after the adoption of the Paris Agreement in 2015. These findings underscore the normative alignment between the ethical foundations of Islamic finance and the environmental commitment of global communities. This study offers important policy implications, including the need for stronger regulatory support, deeper integration of Islamic finance within national climate strategies, and strengthened climate governance within Islamic banks. It also adds to the literature by providing new empirical evidence on the distinctive and evolving role of Islamic banking in supporting macro-level climate resilience. Acknowledgment The first author acknowledges the support of the Securities Commission Malaysia in awarding the fellowship at the Oxford Centre for Islamic Studies, during which this paper was completed.